Answer: A. (x - 4, y - 2)
B. (x + 7, y - 11)
Explanation:
A) How do you get the x-coordinate of 3 to become a x-coordinate of -1? by subtracting 4 --> x - 4
How do you get the y-coordinate of 5 to become a y-coordinate of 3? by subtracting 2 --> y - 2
The transformation is: (x - 4, y - 2)
B) How do you get the x-coordinate of -4 to become an x-coordinate of 3? by adding 7 --> x + 7
How do you get the y-coordinate of 11 to become a y-coordinate of 0? by subtracting 11 --> y - 11
The transformation is: (x + 7, y - 11)